Correction to: Allogeneic hematopoietic stem cell transplantation in two brothers with DNA ligase IV deficiency: a case report and review of the literature - Sarah Schober; Karin Schilbach; Michaela Doering; Karin M. Cabanillas Stanchi; Ursula Holzer; Patrick Kasteleiner; Jens Schittenhelm; Juergen F. Schaefer; Ingo Mueller; Peter Lang; Rupert Handgretinger (BMC, 2019)
After publication of the original article (1), it was brought to our attention that references 24 and 31 are inappropriately cited in the article.